2014
DOI: 10.1016/j.yebeh.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stimulant effects in youth with ADHD symptoms and epilepsy

Abstract: To retrospectively examine response to stimulant treatment in patients with epilepsy and ADHD symptoms as predicted by seizure freedom for six months, use of methylphenidate (MPH) versus amphetamine (AMP) preparations, and cognitive level, medical records were searched for patients under age 18 with epilepsy and ADHD symptoms treated with MPH or AMP (n = 36, age 10.4±3.5; 67% male). “Responders” had a CGI-Improvement score of ≤2 and did not stop medication due to adverse effects. “Worsened” patients discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…One adult-based class III study comparing response to methylphenidate versus amphetamines found greater efficacy in the methylphenidate group. 80 Two class III and one class IV study reviewed response to atomoxetine in a pediatric population with epilepsy and ADHD; 59% and 82% reported benefit, with the remaining study reporting that 37% continued therapy but actual efficacy was not quantified. 78,81,82 In conclusion, Level B evidence supports efficacy of methylphenidate in children with epilepsy and comorbid ADHD.…”
Section: Are There Any Evidence-based Treatment Recommendations Witmentioning
confidence: 99%
“…One adult-based class III study comparing response to methylphenidate versus amphetamines found greater efficacy in the methylphenidate group. 80 Two class III and one class IV study reviewed response to atomoxetine in a pediatric population with epilepsy and ADHD; 59% and 82% reported benefit, with the remaining study reporting that 37% continued therapy but actual efficacy was not quantified. 78,81,82 In conclusion, Level B evidence supports efficacy of methylphenidate in children with epilepsy and comorbid ADHD.…”
Section: Are There Any Evidence-based Treatment Recommendations Witmentioning
confidence: 99%
“…Previous studies have shown that treatment with MPH results in clinically significant decrease of ADHD symptoms in 60-80% of children with epilepsy and ADHD. [7][8][9][10][11][12][13] Although it has been suggested that efficacy of MPH might be lower in patients with idiopathic generalized epilepsy or in patients with predominantly inattentive subtype ADHD, 8 this observation has not been confirmed by others. 7,9 However the sample size of these studies, which ranged from 12 to 33 patients, [7][8][9][10][11][12][13] might have been too small to identify factors associated with response to MPH.…”
mentioning
confidence: 97%
“…2,4,5 Similarly, the clinical determinants of the response to methylphenidate (MPH), the firstline pharmacologic treatment of ADHD with or without epilepsy, 6 remain unknown. 7,9 However the sample size of these studies, which ranged from 12 to 33 patients, [7][8][9][10][11][12][13] might have been too small to identify factors associated with response to MPH. [7][8][9][10][11][12][13] Although it has been suggested that efficacy of MPH might be lower in patients with idiopathic generalized epilepsy or in patients with predominantly inattentive subtype ADHD, 8 this observation has not been confirmed by others.…”
mentioning
confidence: 98%
“…Three randomised, double-blind, placebo-controlled, cross-over trials showed that methylphenidate 0.3-1 mg/kg/day is effective and well tolerated in children with epilepsy and ADHD with response rates ranging between 60% and 70% (73)(74)(75). For amphetamine, there is just a retrospective study of 36 patients with epilepsy and ADHD that compared response rates of amphetamine and methylphenidate and showed a significant improvement in 63% of patients taking methylphenidate versus 24% of those on amphetamine (76).…”
Section: Evidence From Rct In Epilepsymentioning
confidence: 99%